Comparison of lipoprotein (a) serum concentrations measured by six commercially available immunoassays. (October 2019) - Scharnagl, Hubert; Stojakovic, Tatjana; Dieplinger, Benjamin; Dieplinger, Hans; Erhart, Gertraud; Kostner, Gerhard M.; Herrmann, Markus; März, Winfried; Grammer, Tanja B.
Abstract: Background and aims: Lipoprotein (a) [Lp(a)] is an established causal risk factor for cardiovascular disease (CVD), independently of low-density lipoproteins (LDL) and other risk factors. The recognition of Lp(a) as an atherogenic molecule has raised the demand for reliable quantification methods in the clinical laboratory. The aim of this work is to compare commercial immunochemical assays. Methods: We measured Lp(a) serum concentrations using six different assays, providing Lp(a) in mg/dl (Denka Seiken, Abbott Quantia, Beckman, Diasys 21FS, and Siemens N Latex) or in nmol/l (Roche TinaQuant, Diasys 21 FS) in 144 serum samples covering the clinically relevant range of Lp(a) concentrations. All assays relied on five-point calibrations using calibrators provided by the manufacturers. Apolipoprotein(a) phenotyping was performed by sodium dodecyl sulfate-agarose gel electrophoresis (SDS-agarose) followed by immunoblotting. Results: Most bivariate correlation coefficients were greater than 0.90. Compared to an established IFCC-proposed reference material, the results of the different assays diverged from the target values (43.3 mg/dl or 96.6 nmol/l) by −8% (Siemens N Latex) and +22% (Abbott Quantia). Stratification of the samples into five groups with increasing Lp(a) concentrations and difference plots showed that the differences among assays were concentration-dependent. Some assays overestimated Lp(a) at high concentrations compared to the Denka Seiken assay. Conclusions: Current commercial immunological assays for measuring Lp(a) concentrations are differently calibrated. Their biases differ significantly across the clinically relevant concentration range in a non-linear manner. This is not conclusively explained by apolipoprotein (a) phenotypes. Further international efforts to harmonize assays for Lp(a) are needed. Graphical abstract: Image 1 Highlights: - Lipoprotein (a) is an established risk factor for cardiovascular disease - The comparison between commercially available assays revealed substantial differences - Further efforts to harmonize assays for lipoprotein(a) are needed